FUNGSI RITUAL TARI KEMBANGAN JARANAN DOR RESI TURONGGO MELATI DI KOTA BATU - Aliza Nindya Widyanti; Mukhlas Alkaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Kembangan Dance Ritual of Jaranan Dor Resi Turonggo Melati in Batu City is a ritual dance that belongs to the category of folk dance. This ritual is perfomed every Friday Legi, during village cleansing ceremonies, and in various ritual events as part of a traditional belief passed down earlier generations. It is believed to ward off misfotune, provide spiritual protection, andhonor the sacred guardian of Punten village. As a form of folk dance, the Kembangan Dance Ritual of Jaranan Dor Resi Turonggo Melati exhibits distinctive characteristics, including strong elements of religion, mysticism, customs, and comunity traditions. The selection of this ritual dance as the subject of this study is based on its functions and forms, which have attracted the researcher’s interest of the examine it using a qualitative method with an ethnocoreological approach. The results of the study indicate that the functions of the Kembangan Dance Ritual of Jaranan Dor include serving as a ritual medium, a vehicle for expressing both secular and religious rites, and a form of entertainment and public spectale. Meanwhile, the form of the ritual dance encompasses movement, dancers, costumes, floor pattems, dance music, and the perfomance space.